Rehabilitation of patients with spondyloarthritis: a narrative review - Simeon Grazio; Frane Grubišić; Vedran Brnić (Medicinski glasnik, 2019)
Nonpharmacological interventions are one of the mainstreams of treatment for patients with spondyloarthritis (SpA). They include education, measures regarding joint protection, posture and rest, therapeutic exercise, physical therapy modalities, orthoses, and acupuncture. A key component in the rehabilitation of patients with SpA entities is therapeutic exercise, which can be performed as land-based or water-based. Positive effects of the exercises are manifested in reducing pain, maintaining mobility, improving posture, increasing aerobic capacity and improving quality of life. The best effects can be obtained when exercise is performed under the supervision of a physiotherapist at a health institution. The majority of studies on therapeutic exercise in SpA are related to ankylosing spondylitis (AS), while there is a paucity of studies devoted to other conditions. Although progress has been made in the quantity and quality of research on this topic, there are still issues regarding the quality of studies and considerable variability among them, which makes it difficult to compare different methods and harmonize and develop rehabilitation protocols according to evidence-based medicine.
Keywords: exercise; physical therapy modalities; rehabilitation; spondylarthritis rehabilitation